Ts’akiel. Vestidos rituales, prácticas de transfiguración y temporalidades superpuestas en la fiesta del k’in tajimol (Chenalhó y Polhó, Chiapas) - Rocío Noemí Martínez G. (Journal de la Société des Américanistes)
The purpose of this article is to analyze the textiles (woven and embroidered), artifacts and iconography that characterize so-called ts’akiel ritual garments during the Tsotsil people’s K’in Tajimol festival, which takes place in Chenalhó and Polhó (respectively a constitutional municipality and an autonomous municipality in Chiapas, Mexico, which are compared here). Their shapes, materials and materiality involve distinct mnemonic procedures reflecting different aspects of the conception of the person and of the territorial and political membership group. These ritual garments “contain the history of the ancestors,” which is embodied at the festival by those who dress in this “other skin.” Each layer of the ts’akiel is embroidered with animal, plant or human motifs that contain “the eyes of ch’ulel”, that is to say “the souls that inhabit the clothes.” These will reveal “the body’s other,” not only flesh and bones, but also all of the person’s experiences, that is, the constantly reconfigured multiple entities and stories that make up the person.